PharmaChain: A blockchain to ensure counterfeit‐free pharmaceutical supply chain. Issue 2 (5th July 2022) - Bapatla, Anand K.; Mohanty, Saraju P.; Kougianos, Elias; Puthal, Deepak; Bapatla, Anusha
Abstract: Globalisation has facilitated different industries to eliminate geographical boundaries and equipped organisations to work collectively to produce goods. Pharmaceuticals is one such industry which has majorly benefited from globalisation to reduce costs and increase profitability at different aspects of research, development, manufacturing of drugs and finally distribution of drugs. Globalisation not only reduces costs and increases profits for the industry, it also makes essential medication available to all individuals even at remote areas of undeveloped, developing and developed countries. As the number of entities or participants grew in the Pharmaceutical Supply Chain (PSC), the complexity and abstractness of the drug delivery from manufacturer to consumer has increased, which raised new concerns like counterfeit medication, incorrect, incomplete or no information about the drug reaching the consumer thus undermining customer confidence and most importantly distribution delays which can cause serious impact on the life of the consumer as well as business growth. Considering all these challenges, there is a dire need for a robust PSC which can eliminate blind parties and provide a transparent chain. A transparent PSC will eliminate data fragmentation between different participating entities by creating a trail of secure, single source of truth for the entire life cycle of a medicine, thereby eliminating the introduction of counterfeits and ensuring the consumer safety. This article proposes a novel Distributed Ledger Technology (DLT) based transparent supply chain for PSC and proof‐of‐concept is implemented to analyse the scalability and efficiency of the proposed architecture. Distributed Ledger Technology (DLT) is one of the technologies which can provide such transparent PSC and Smart Contracts (SC) are the most commonly used component in such systems to implement business logic and access control mechanisms. The proposed PharmaChain model investigates all the interactions between the main entities in PSC and also addresses smart contract issues such as re‐entrance, randomness and lacking trustworthy data feed. Results are compared with other proposed solutions for PSC based on DLT.